Negócio jurídico processual ambiental: diálogo, sustentabilidade e desenvolvimento - Cibils, Patrícia Maldaner (Universidade do Vale do Rio dos Sinos, 2024)
The research aims to explain the scenario of environmental degradation, with the disorderly growth of urban centers and the dichotomy between economic development and environmental protection, with multiple consequences, among which social vulnerability stands out. In this scenario, numerous collective suits emerge with the goal of promoting environmental protection. Nevertheless, through traditional adversarial methods of the judicial process, it is sometimes not possible to obtain the desired protection effectively. Thus focusing the research problem on the excessive judicialization of topics whose nature transcends the concept of parties itself, in addition to demanding a multidisciplinary approach and the expansion of dialogue. Among the demands is SL 15/75/STF, which originates from a colective suit that aims to protect an enviromental area called Padre Balduino Rambo, whose area covers the municipalities of São Leopoldo and Sapucaia do Sul, being the case study on which the look into the research. Hence, the question is how to contribute to the resolution of occurring legal actions involving environmental suits within the urban setting of the metropolitan region of Porto Alegre, with substantial impacts on the lives of the litigants? In light of this question, we seek to further the study of an existing instrument in the national legal system, that is, the procedural legal transaction provided for in the Code of Civil Procedure, aiming, through self-regulation of the procedure to adjust it to achieve steps compatible with the measures designed by the parties to protect the environment. The general objective of the study is to show that dialogue has been transforming the culture of litigation through the adequate resolution of conflicts in the form of procedural legal business and, with this, the autonomous reestablishment of peace by the parties. The specific objectives focus on: (i) the contextual examination of multidisciplinary topics that are specific to environmental demands; (ii) the examination of the case study (SL no. 1,575 of the STF), which involves the discussion about the urban environment in the District of Porto Alegre; (iii) presenting the possible results of the procedural legal transaction as a way of resolving disputes and restoring peace between the parties; and, (iv) presenting, as an applied delivery of the research result consistent with the “framework” of the environmental legal business, the relevance of the research concentrated on the legal uncertainty caused by the judicialization of environmental conflicts, which ends up removing investments and the possibility of applying resources that could transform the landscape in a sustainable way.
Keywords: Meio ambiente; Negócio; Judicialização; Resolução; CPC; SL 1575; Environment; Contract procedure; Judicialization; Resolution; ACCNPQ::Ciências Sociais Aplicadas::Direito